2012
DOI: 10.4103/1947-2714.92905
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of causes and patterns of recurrent varicose veins after surgery

Abstract: Background:Varicose vein surgery is characterized by high recurrence rate of 60% after 5 years of follow-up observation, and this is a disappointing finding, both for the patient and surgeon.Aim:To identify the possible causes and patterns of recurrent varicose veins.Materials and Methods:92 patients with recurrent varicose veins were enrolled in this study. Full detailed history, examination, and investigations were done.Results:30 patients had recurrence after saphenofemoral disconnection, 22 patients with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Relatively similar morphological configurations were observed by Talalwah et al (2014) and Abhinitha et al (2017) [10][11]. Gad et (2013) reported that 15.2% of patients with recurrent varicose were having a double long saphenous venous system [12]. GSV plays an important role in the venous return of the lower extremity because of numerous tributaries and it has relations with deeper veins.…”
Section: Case Reportsupporting
confidence: 67%
“…Relatively similar morphological configurations were observed by Talalwah et al (2014) and Abhinitha et al (2017) [10][11]. Gad et (2013) reported that 15.2% of patients with recurrent varicose were having a double long saphenous venous system [12]. GSV plays an important role in the venous return of the lower extremity because of numerous tributaries and it has relations with deeper veins.…”
Section: Case Reportsupporting
confidence: 67%